Leveraging Market Basket Analysis to Develop Sales Strategies for MSMEs: a Case Study of Los in Between - Satya Fajar Gumelar; Ega Adrianto; Alfilia Hilda Rahmatika (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Micro, Small, and Medium Enterprises (MSMEs) a cornerstone of Indonesia’s economic, contributing approximately 61% to the national GDP (Haryo Limanseto, 2022). However, MSMEs, particularly in the competitive Food and Beverage (F&B) sector, face persistent challenges including limited access to capital, technological adoption gaps, and volatile consumer preferences (Badan Pusat Statistik, 2023). These factors make revenue stability a critical issue. Purpose:  Through a case study of LOS In Between, this research aims to: (1) demonstrate the application of MBA in a resource-constrained, offline MSME setting; (2) identify product associations to inform bundling and upselling strategies for the business; and (3) propose a replicable analytical approach that can be adapted by other small-scale F&B businesses to enhance sales performance. This study aims to analyze consumer purchasing patterns through Market Basket Analysis (MBA) and to provide actionable data-driven strategies to improve sales performance and competitiveness in MSMEs. Design/methodology/approach: This study applies Market Basket Analysis using the Apriori algorithm to transactional data from LOS In Between (January–June 2025). Association rules derived from support, confidence, and lift metrics were translated into practical sales strategies—including bundling, upselling, and cross selling. Findings/Result: The analysis revealed that STM functions as an anchor product frequently purchased with items such as SJ and WF, making it ideal for strategic bundling. Products with weaker associations, such as CMM, were considered more suitable for upselling promotions. The findings show that even MSMEs with modest transaction volumes can leverage simple data analytics to uncover purchasing patterns, optimize sales, and enhance customer experience. Conclusion: MBA provides a practical and scalable analytical tool for MSMEs to design evidence-based sales strategies. By leveraging transaction data, MSMEs can increase revenue, strengthen customer engagement, and sustain competitiveness in dynamic market environments.Originality/value (State of the art): This study addresses the gap by adapting Market Basket Analysis to a micro-scale F&B, LOS In Between. Its novelty lies not only in applying MBA to this constrained setting but also in proposing a practical methodology that converts association rules into actionable strategies like bundling and upselling, designed for periodic re-mining to track preference shifts. The research also outlines how MBA can be integrated with lightweight decision frameworks suitable for MSMEs, providing localized evidence from Indonesia’s F&B sector.  Keywords:   market basket analysis, sales strategies, msmes, apriori, purchase patterns